Tricky lipoma or bad neighborhood: a case of ileocolic intussusception - Rouxinol, Margarida Pires de Moura da Silva; Gualter Batista, Maria; Ribeiro, Juliana; Martins, Daniela; Melo, Ana; Silva, Sílvia; Costa, Pedro; Moreira, Herculano; Pinto-de-Sousa, João (International Surgery Journal, 2025)
Colonic lipomas (CLs) are an infrequent, benign, non-epithelial, adipose tissue tumour. Most of the CLs are asymptomatic, but around 25% of patients may develop symptoms, such as ileocolic intussuception. Surgical or endoscopic resection of the lesion is the treatment of choice. We present a case of ileocolic intussusception caused by colonic lipoma in an adult patient. The patient underwent surgical resection, and the diagnosis was confirmed by histopathological examination of the specimen.